The fourth instance theory in the international process of investigating human rights violations (Revista do Tribunal Regional Federal da 3ª Região, 2021)
The purpose of this paper is to research the so-called fourth instance formula within the scope of international mechanisms for the protection of human rights. Our objective is to demonstrate that the theory of the fourth instance – adopted by the European and American regional systems for the protection of human rights – reveals itself as limit reserved for the analysis and investigation of human rights violations by States, serving as a procedural condition and even as a requirement of admissibility for processing and investigating alleged violations. By making a brief study of the conditions necessary to seek the collective or institutional mechanisms for measuring human rights violations, we intend to demonstrate that, although it presents itself as a restriction or limit, the theory of the fourth instance is a relevant means of insurgency against illegalities or arbitrariness practiced in due legal process, invocable not as an appeals procedure but as a legitimate and internationally recognized procedural means against violations of human rights.
Keywords: theory of the fourth instance; international responsibility; human rights; exhaustion of domestic remedies